(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the structural-semantic and functional-stylistic characteristics of oxymorons in Uzbek artistic discourse. An oxymoron is regarded as a stylistic figure that emerges through the combination of semantically contradictory units within a single syntactic structure. The study examines the mechanisms of oxymoron formation, their syntactic patterns, and their role in enhancing emotional and expressive effects in literary texts. Furthermore, the realization of oxymorons at different linguistic levels, including sentence constituents, word combinations, simple sentences, and complex sentences, is analyzed through illustrative examples. The findings indicate that oxymorons constitute one of the important syntactic-stylistic devices that reveal the expressive potential of the Uzbek language.